The Ecology and Evolutionary Biology of Cancer: A Review of Mathematical Models of Necrosis and Tumor Cell Diversity - John D. Nagy (Mathematical Biosciences and Engineering)
Recent evidence elucidating the relationship between parenchyma cells and otherwise ''healthy'' cells in malignant neoplasms is forcing cancer biologists to expand beyond the genome-centered, ''one-renegade-cell'' theory of cancer. As it becomes more and more clear that malignant transformation is context dependent, the usefulness of an evolutionary ecology-based theory of malignant neoplasia becomes increasingly clear. This review attempts to synthesize various theoretical structures built by mathematical oncologists into potential explanations of necrosis and cellular diversity, including both total cell diversity within a tumor and cellular pleomorphism within the parenchyma. The role of natural selection in necrosis and pleomorphism is also examined. The major hypotheses suggested as explanations of these phenomena are outlined in the conclusions section of this review. In every case, mathematical oncologists have built potentially valuable models that yield insight into the causes of necrosis, cell diversity and nearly every other aspect of malignancy; most make predictions ultimately testable in the lab or clinic. Unfortunately, these advances have gone largely unexploited by the empirical community. Possible reasons why are considered.